Experiências narradas por homens no exercício da paternidade: rompendo paradigmas - Glaucia Resta Dal-Rosso; Silvana de Oliveira Silva; Greice Machado Pieszak; Sandra Beatris Diniz Ebling; Vanessa do Nascimento Silveira (Universidade Federal de Santa Maria, 2019)
To know the experiences of men in the exercise of paternity. Method: a descriptive-exploratory study with a qualitative approach, conducted with 15 men who accompanied their partners in a course for pregnant women. The production of data occurred through a narrative interview and the analysis of thematic content. Results: the men in this study experienced paternity actively, helping to care for their children in relation to maintaining basic needs and education. The experiences generated personal impacts such as interest in self care and the search for information to qualify the exercise off paternity. Final considerations: nursing can contribute to strengthening the exercise of paternity through actions that value the care and insertion of men in the health system